2020
DOI: 10.18498/amailad.781299
|View full text |Cite
|
Sign up to set email alerts
|

Öğrencilerin Kitap Okuma Tutumları ile Kitap Okumanın DKAB Öğretim Programındaki Değerlere Etkisi Arasındaki İlişkinin İncelenmesi

Abstract: İntihal / Plagiarism: Bu makale, en az iki hakem tarafından incelendi ve intihal içermediği teyit edildi. / This article has been reviewed by at least two referees and scanned via a plagiarism software. Bu araştırma, Yakın Doğu Üniversitesi Bilimsel Araştırmalar Etik Kurulu'nun 24.04.2020 tarih ve YDÜ/EB/2020/469 proje numaralı izni ile uygulanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The first step was to check if there was a difference between boys and girls in terms of the seven dispositional facets of critical thinking and we discovered that girls performed significantly much better than boys in most of the facets except for truth-seeking. A similar finding was observed in a recent study conducted in TRNC and girls' performances on reading skills were found to be better than boys (Koç, 2020 ). Koç asserted that reading skills are also associated with critical thinking.…”
Section: Discussionsupporting
confidence: 90%
“…The first step was to check if there was a difference between boys and girls in terms of the seven dispositional facets of critical thinking and we discovered that girls performed significantly much better than boys in most of the facets except for truth-seeking. A similar finding was observed in a recent study conducted in TRNC and girls' performances on reading skills were found to be better than boys (Koç, 2020 ). Koç asserted that reading skills are also associated with critical thinking.…”
Section: Discussionsupporting
confidence: 90%